METODE LEMBAGA KESEJAHTERAAN SOSIAL ANAK (LKSA) PANTI ASUHAN NURUL FATIMAH DALAM MENGEMBANGKAN POTENSI DIRI REMAJA DI KELURAHAN PACCINONGANG KECAMATAN SOMBA OPU KEBUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The journal aims to describe how the method of the children's social welfare institution Nurul Fatimah Orphanage in developing adolescent potential. The results of this study show that the efforts of the Nurul Fatimah Orphanage Children's Social Welfare Institute in developing adolescent self-potential can be seen in terms of education by sending children to formal education, opening tutoring classes, and opening religious education classes. Art fields such as poetry, storytelling, motivation, dancing, and mc) and sports namely gymnastics and badminton. Supporting factors are external and internal factors, and inhibiting factors are different backgrounds, family, and community assumptions.